1995
DOI: 10.1002/jat.2550150608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lymphocyte proliferation by immunohistochemistry in the local lymph node assay

Abstract: A modified version of the local lymph node assay (LLNA) is presented, using bromodeoxyuridine to label proliferating lymphocytes. Cell counting is done on mid-sagittal sections of individual nodes under light microscopy. Two irritants (sodium lauryl sulfate and salicylic acid), four allergens of various sensitizing potential (potassium dichromate, 4-chloroaniline, neomycin sulfate and nickel sulfate) and one chemical of unknown sensitizing potential (ethyl 3-aminobenzoate) were tested either in the short proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Flow cytometric analysis and immunohistochemical assays have been developed to count BrdU incorporation into lymph node cells (Boussiquet-Leroux et al, 1995;Lee et al, 2002, Suda et al, 2002. Takeyoshi et al (2001) investigated BrdU incorporation into lymph node cells by using a cell proliferation ELISA kit but their results for a number of allergens suggested an insufficient sensitivity because the increase in lymph node cell counts was not taken into account when calculating SI values (Takeyoshi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric analysis and immunohistochemical assays have been developed to count BrdU incorporation into lymph node cells (Boussiquet-Leroux et al, 1995;Lee et al, 2002, Suda et al, 2002. Takeyoshi et al (2001) investigated BrdU incorporation into lymph node cells by using a cell proliferation ELISA kit but their results for a number of allergens suggested an insufficient sensitivity because the increase in lymph node cell counts was not taken into account when calculating SI values (Takeyoshi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(This was obtained with 20% Salicylic Acid.) Boussiquet-Leroux et al (1995) reported results of an LLNA performed using 5% to 20% Salicylic Acid dissolved 4:1 in acetone-olive oil (AOO). Groups of four female CD1 mice were dosed on the dorsum of the external ears with 25 µl of the test solution or the vehicle once daily on days 1 to 3.…”
Section: Salicylic Acidmentioning
confidence: 99%
“…To assess skin sensitization, murine local lymph node assays (LLNAs), which require relatively few animals in consideration of animal welfare, have been extensively used (Kimber and Weisenberger, ; OECD, ; Klink and Meade, ; Vandebriel et al , ). Although the standard LLNA endpoint is determination of the degree of 3 H‐methyl thymidine incorporation into lymphocytes (Boussiquet‐Leroux et al , ; Homey et al , ; Takeyoshi et al , ; Suda et al , ), alternative methods and endpoints have been used to reduce the number of animals or exclude the use of radioactivity. To this end, other clinical data, such as ear thickness, lymph node (LN) weight and cell counts, have been used as toxicological endpoints for assessment of chemical sensitizing potential (Homey et al , ; Vohr et al , ; Ehling et al , 2005a, b; Ku et al , ).…”
Section: Introductionmentioning
confidence: 99%